Performance of mutant greengram (Vigna radiata) genotypes for South eastern Coastal Plain Zone of Orissa - BAISAKH, B; SENAPATIl, N (The Indian Journal of Agricultural Sciences, 2011)
The mean square for genotypes was significant for both the years indicating significant variability among the 21 genotypes of greengram [Vigna radiata (L.) Wilczek]. The growing condition was heterogenous due to significant mean squares. Significant Genotype X Year indicated differential response of genotypes to environment. 'OUM 7' and 'QUM 11-5' were found to be promising and suitable mutants for South-eastern Coastal Plain Zone of Orissa in place of 12 standard varieties of greengram during rainy season.